There is a step in what seems to be the standard derivation of the Euler-Lagrange equation that I do not see how can be justified (it is the first derivation in the Wikipedia article on the equation).

We have that $g(\epsilon) = f(t) + \epsilon \lambda(t)$

We are computing the total derivative $\frac{\partial F}{\partial\epsilon}(t,g(\epsilon),\dot{g}(\epsilon))$ and get that this is equal to $\frac{\partial F}{\partial g}\lambda(t) + \frac{\partial F}{\partial \dot{g}}\dot{\lambda}(t)$. The thing that does not make sense to me is that this is supposed to equal $\frac{\partial F}{\partial f}\lambda(t) + \frac{\partial F}{\partial \dot{f}}\dot{\lambda}(t)$ at $\epsilon = 0$.

To make some sense of it, I tried using the definition of the derivative on $\frac{\partial F}{\partial g}\lambda(t)$ to see if I can make it equal $\frac{\partial F}{\partial f}\lambda(t)$. However, what I do get is: $$\lim_{\Delta \epsilon \to 0}\frac{F(t,f(t)+(\epsilon+\Delta \epsilon) \lambda(t),\dot{g}) - F(t,f(t)+ \epsilon \lambda(t),\dot{g})}{\Delta \epsilon }$$ $$=\lim_{\Delta \epsilon \to 0}\frac{F(t,f(t)+(\epsilon+\Delta \epsilon) \lambda(t),\dot{g}) - F(t,f(t)+ \epsilon \lambda(t),\dot{g})}{\Delta g } \frac{\Delta g}{\Delta\epsilon}$$ Here we have that $\Delta g = \Delta \epsilon \lambda(t)$. This gives me: $$=\lim_{\Delta \epsilon \to 0}\frac{F(t,f(t)+(\epsilon+\Delta \epsilon) \lambda(t),\dot{g}) - F(t,f(t)+ \epsilon \lambda(t),\dot{g})}{\Delta g } \lambda(t)$$

Now I am just stuck. I cannot convince myself that $\Delta g = \Delta f$. I mean, the derivation is with respect to $\epsilon$, not t. So, why does this lead to the Euler-Lagrange equation?


I think I may have to clarify my problem: $\frac{\partial F}{\partial f} \lambda$ looks to me to be equal to: $$\lim_{\Delta f \to 0}\frac{F(t,f(t)+\Delta f(t),\dot{g}) - F(t,f(t),\dot{g})}{\Delta f(t) } \lambda(t)$$

However, my computations above imply that the solution is $$\lim_{\Delta \epsilon \to 0}\frac{F(t,f(t)+(\epsilon+\Delta \epsilon) \lambda(t),\dot{g}) - F(t,f(t)+ \epsilon \lambda(t),\dot{g})}{\Delta g } \lambda(t) = \lim_{\Delta \epsilon \to 0}\frac{F(t,f(t)+\Delta \epsilon \lambda(t),\dot{g}) - F(t,f(t),\dot{g})}{\Delta \epsilon \lambda(t) } \lambda(t) $$

Clearly, my reasoning and computations are wrong. However, I don't see how I can get the solution above by computing $\frac{dF}{d\epsilon}$.

  • 1
    $\begingroup$ The answer here might help you a bit. $\endgroup$ – user99914 Aug 3 '17 at 6:52

It's just the chain rule. You are given a function $F(\cdot,\cdot,\cdot):{\mathbb R}^3\to{\mathbb R}$ of three variables, say $t$, $p$, $q$, and then are studying the expression $$F\bigl(t,f(t),\dot f(t)\bigr)$$ for various known or unknown "test functions" $t\mapsto f(t)$. In particular you form the expression $$\psi(\epsilon):=F\bigl(t,f(t)+\epsilon g(t),\dot f(t)+\epsilon\dot g(t)\bigr)\ .$$ Then for any fixed $t$ you have $$\psi'(\epsilon)=F_{.2}\bigl(t,f(t)+\epsilon g(t),\dot f(t)+\epsilon\dot g(t)\bigr) \>g(t)+F_{.3}\bigl(t,f(t)+\epsilon g(t),\dot f(t)+\epsilon\dot g(t)\bigr)\>\dot g(t)\ .\tag{1}$$ Note that you do not "differentiate $F$ with respect to $f$" here. It is an abuse of notation to write ${\partial F\over\partial f}$, but we have learnt to live with it. $F$ has known partial derivatives $F_{.i}$ at each point $(t,p,q)\in{\mathbb R}^3$ before any "test function" $f$ is inserted.

Put $\epsilon:=0$ in $(1)$ and obtain $$F_{.2}\bigl(t,f(t),\dot f(t)\bigr) \>g(t)+F_{.3}\bigl(t,f(t),\dot f(t)\bigr)\>\dot g(t)\ .$$

| cite | improve this answer | |
  • $\begingroup$ Well, that does not address the issue I am having. I understand it's the chain rule I am working with. The thing is, like you said, t is fixed, and f depends on t and not $\epsilon$. So, I don't understand how dF/df and dF/df' can be anything other than 0 in the equation dF/d$\epsilon$ (at least, the way it is derived in the proof I am referencing). I may have to edit my original question. $\endgroup$ – Avatrin Aug 3 '17 at 8:46
  • $\begingroup$ I see you have edited your answer. Isn't dF/df = $\lim{x \to a} \frac{F(f(x)) - F(f(a))}{f(x)-f(a)}$? Isn't that, in terms of calculation, differentiating F with respect to f? I hope this is not too much to ask, but can you show me why the step is true using the definition of the derivative? Or, do you know a website or book where I can find this computation having been done? Preferably with explanations.... $\endgroup$ – Avatrin Aug 3 '17 at 12:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.